Influence of Social Media on Student Academic Achievement Based on K-Means to Support Indonesia Emas 2045 - Himawan, Arif; Linawati, Linawati; Asnawi, Choerun; Subekti, Dayat; Setiawan, Chanief Budi (Emerging Information Science and Technology, 2025)
Social media is a digital platform used as a means of communication through text, images,videos, and information exchange. Among students, social media is often used beforelectures, during breaks, and after teaching and learning activities. This study aims toanalyze social media usage patterns and their impact on student academic achievement,particularly at the Faculty of Engineering and Information Technology (FTTI) of JenderalAchmad Yani University Yogyakarta (Unjaya). The method applied is the K-Meansalgorithm to identify social media usage patterns and their correlation with academicachievement. The research stages included data collection, data pre-processing,application of the K-Means algorithm, evaluation, and conclusion of results. Based on asample of 107 students using the Elbow method, three data clusters were obtained, namelyCluster 0 (3 members), Cluster 1 (47 members), and Cluster 2 (57 members). Testing usingthe Silhouette Score produced a value of 0.196, while the Davies-Bouldin Index showed avalue of 1.490. The results indicate that social media use has a positive impact on learningachievement, as reflected in the Grade Point Average (GPA) above 3.6 among FTTI Unjayastudents